Enterococcus faecalis Isolated From Infant Feces Inhibits Toxigenic Clostridioides (Clostridium) difficile - Romyasamit, Chonticha; Thatrimontrichai, Anucha; Aroonkesorn, Aratee; Chanket, Wannarat; Ingviya, Natnicha; Saengsuwan, Phanvasri; Singkhamanan, Kamonnut (Frontiers in Pediatrics, 2020)
This study aims to identify potential probiotic enterococci strains that act against Clostridioides (Clostridium) difficile strains and exert a protective effect on HT-29 cells. To this end, nine Enterococcus strains isolated from the feces of breast-fed infants were investigated. They were identified as E. faecalis. The probiotic properties including their viabilities in simulated gastrointestinal condition, cell adhesion ability and their safety were evaluated. All strains exhibited more tolerance toward both pepsin and bile salts and adhered more tightly to HT-29 cells compared with the reference probiotic strain Lactobacillus plantarum ATCC 14917 (TISTR 877). Six of nine strains carried at least one virulence determinant gene; however, none exhibited virulence phenotypes or carried transferable antibiotic resistance genes. These strains did not infect G. mellonella when compared to pathogenic E. faecalis strain (p < 0.05). Moreover, their antibacterial activities against C. difficile were examined using agar well diffusion, spore production, and germination tests. The six safe strains inhibited spore germination (100 − 98.20% ± 2.17%) and sporulation, particularly in C. difficile ATCC 630 treated with E. faecalis PK 1302. Furthermore, immunofluorescence assay showed that the cytopathic effects of C. difficile of HT-29 cells were reduced by the treatment with cell-free supernatant of E. faecalis strains. These strains prevented rounding of HT-29 cells and preserved the F-actin microstructure and tight junctions between adjacent cells, which indicated their ability to reduce the clostridial cytopathic effects. Thus, our study identified six E. faecalis strains that displayed anti-C. difficile activity. These could be promising probiotics with potential applications in the prevention of C. difficile colonization and treatment of CDI.